Verification in the Issuing State of Evidence Obtained on the Basis of the European Investigation Order - Steinborn, Sławomir; Świeczkowski, Dawid (Review of European and Comparative Law, 2023)
The aim of this article is to address the issue of the extent of incorporation and verification of evidence for purpose of the criminal trial as the evidence base for the judgement, namely the evidence that is obtained on the basis of the European Investigation Order, including the evidence obtained in various forms that may raise doubts in terms of the protection of individual rights. The authors would like to focus on the analysis from the perspective of the Directive 2014/41/EU of the European Parliament and of the Council of 3 April 2014 on the European Investigation Order in criminal matters and Polish legislation, and consider what kind of possibilities the issuing state’s authorities have to verify admissibility of evidence, especially the way in which the evidence is obtained when it has not been produced upon request but only delivered since it has already been in possession of the executing state’s authorities.